2021
DOI: 10.1093/heapro/daab032
|View full text |Cite
|
Sign up to set email alerts
|

Information, control and health promotion in the Brazilian context of the pandemic

Abstract: Summary This article discusses how preventive and promotional discourses have been incorporated by the Brazilian population in the context of the coronavirus pandemic. It analyzes materials posted on the internet and social after the first case of COVID 19-related death in Brazil that are related health promotion and COVID-19 aimed at orienting society’s response to the pandemic. The analysis considers two key factors: the mismanagement of the pandemic by the Brazilian government and infodemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“… 29 However, as for the control of the pandemic, each country was influenced by the complex dynamics of internal policy and loco-regional inequalities to which they were inserted. 30 Brazil, being the largest country in South America, faced severe consequences of a national policy that did not adequately address the pandemic in a timely manner 31 and, with high contamination rates, in the medium to long term, a high prevalence of post-COVID conditions is expected. A Brazilian cohort identified that after 120 days of the acute phase of COVID-19, 80% of patients had persistent symptoms, the most prevalent being fatigue, dyspnea, cough, headache, and loss of muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“… 29 However, as for the control of the pandemic, each country was influenced by the complex dynamics of internal policy and loco-regional inequalities to which they were inserted. 30 Brazil, being the largest country in South America, faced severe consequences of a national policy that did not adequately address the pandemic in a timely manner 31 and, with high contamination rates, in the medium to long term, a high prevalence of post-COVID conditions is expected. A Brazilian cohort identified that after 120 days of the acute phase of COVID-19, 80% of patients had persistent symptoms, the most prevalent being fatigue, dyspnea, cough, headache, and loss of muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…attitudes and behavior were condemned or viewed as inappropriate, and included: gathering in large crowds, taking face-to-face pictures, speaking in close proximity to others, and disrespecting the recommended minimum distance 10 . Unfortunately, these protests are supported by the president and their team, who ignores basic scientific recommendations, and continues to represent the greatest threat to Brazil's response to COVID-19 11 .…”
Section: Highlightsmentioning
confidence: 99%
“…These processes of misinformation from part of our governmental representants make the work of scientists and scientific communication very tricky and challenger. The president has several times questioned the efficacy of COVID-19 vaccines, support unproven therapies 10,12 , and promoted pseudoscience, he had not available to be vaccinated, and also dis a public announce that he will be the last Brazilian to receive the vaccine. As far as we know, based on the age group, he could have done it for more than 3 months.…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse sentido, há uma sofisticação de estratégias no sentido de culpabilização dos indivíduos, desconectadas de uma perspectiva coletiva. Apesar disso, são construídas estratégias que buscam promover condições de saúde equitativas, a partir de potencialidades de cada território, que fortalecem a promoção da saúde como referência para a defesa da vida (Franceschini et al, 2022).…”
Section: Introductionunclassified